Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.7745/kjssf.2012.45.6.925
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibition of Cucumber by Absorbing Excess Al at Low Soil pH

Abstract: On-site diagnosis applied to soil having a symptom of yellowing and whitening in cucumber leaf and stem. Soil pH determined 4.2 by methods of on-site analysis and 4.5 by soil test analysis. High aluminum in soil solution extracted with water saturation was detected. Leaf and stem tissue were abundant in Al content but not in Ca. Also, N content of leaf and stem was low compared to normal N ranges. This symptom of cucumber assumed to be from the Al and nitrous acid gas toxicity by low soil pH and Eh. Conclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In this study, in the acid soil prepared for high rate of denitrification, 36.4 mg N kg -1 of NO2 -was found even after the 5 days of incubation (Table 4). Thomsen et al (1994) (Kim et al, 2010(Kim et al, , 2012. Although NO2 emission and its damaging effect were identified in the wet acid soils containing NO3 -, NO2 -accumulation and NO2 production were completely inhibited when the soil was sterilized (Table 5 and 6).…”
Section: No2mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, in the acid soil prepared for high rate of denitrification, 36.4 mg N kg -1 of NO2 -was found even after the 5 days of incubation (Table 4). Thomsen et al (1994) (Kim et al, 2010(Kim et al, , 2012. Although NO2 emission and its damaging effect were identified in the wet acid soils containing NO3 -, NO2 -accumulation and NO2 production were completely inhibited when the soil was sterilized (Table 5 and 6).…”
Section: No2mentioning
confidence: 99%
“…Also NO2 gas injury was found in fig trees grown in containers with application of nutrient solution containing 200 mg N L -1 of NO3 -, and pH of the artificial soil in the containers was 5.5 (Kim et al, 2010). Kim et al (2012) reported NO2 gas injury in cucumber plants grown in acid soil (pH 4.8) of plastic film house where soil NO3 content was 500 mg L -1 . Considering those incidences of NO2 gas damage to crop plants, NO2 emission is closely related to the NO3 -applied as a nitrogen fertilizer and also to the acidic soil pH.…”
Section: Introductionmentioning
confidence: 99%